PREVENTION AND INHIBITION OF ENVIRONMENTAL BIOFILMS: FUTURE PERSPECTIVES - DEEPA MADATHIL; RAJENDRAN N (International Journal of Pharma and Bio Sciences, 2013)
Biofilm formation is a universal phenomenon pertaining to a microorganism attaching itself to a surface that is in constant contact with water. It occurs widely on the ships hulls, dentures, eyes due to non compatible contact lenses, implanted medical devices, showers tubes, cooling pipes in nuclear reactors, water distribution systems etc. Environmentally and economically viable solutions are increasingly being researched to prevent and control the biofilm formation. Natural and synthetic compounds have been studied extensively to address the issue. This paper reviews the use of various methods being adopted to prevent and inhibit the formation of biofilms and other futuristic approaches.